The Application of Democratic Principles in Indonesia's Electoral System - Anang Syarif Hidayat; Atma Suganda; Supot Rattanapun (LAW & PASS: International Journal of Law, Public Administration and Social Studies, 2024)
This study aims to analyse the application of democratic principles in Indonesia's electoral system, focusing on the suitability of the implementation of the Direct, General, Free, Honest and Fair principle and the factors that hinder the effectiveness of its implementation. The results show that although Indonesia has adopted democratic principles in the organisation of elections, there are some challenges, such as the practice of money politics, unequal access to voters, and low voter participation. However, overall, the principle of Direct, General, Free, Honest and Fair has been applied in various stages of the election, and the role of organising bodies such as the General Election Commission and the General Election Supervisory Agency has increased transparency and accountability. Nonetheless, there is a need to continue improving electoral mechanisms to address existing problems and improve the quality of Indonesian democracy. This research provides recommendations for the strengthening of political education, the application of technology in elections, as well as an evaluation of the threshold policy and the role of mass media in voter education.